PEMETAAN DAERAH ALIRAN SUNGAI LELEMA DAN KONDISI FISIK JARINGAN IRIGASI DI DESA POPONTOLEN BERBASIS SISTEM INFORMASI GEOGRAFIS - Kristianto Pisu; Daniel P.M Ludong; David p. Rumambi (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ The watersheds is an ecosystem and the main elements of this ecosystem are natural resources (land, water and vegetation) and human resources that utilize natural resources. Regarding with the relationship between watershed and irrigation as one component in the water resources management, watersheds determine the availability of irrigation water when the watershed ecosystem is disrupted. In this condition, the water supply for irrigation decreased and therefore the agricultural productivity reduced. The area of the Lelema Watershed is 3,095 ha with a main river as long as 12,787 m that ends in the main river of Nimanga. The irrigated area of the Popontolen village is geographically located in the irrigation areaÂ of Popontolen Village that is located at 1o15'47